Analisis Faktor-Faktor Yang Mempengaruhi Keberhasilan Manajemen Proyek Informatika Di Organisasi - Agung Wijoyo; Nurhalimah Syarifuddin; Sri Nurhasanah; Mohamad Yudha Mauluda; Teguh Wiyono; Bagas Harizunar (CV. Multi Kreasi Media, 2023)
In analyzing the factors that influence the success of informatics project management in organizations, there are several things that practitioners and academics in the field of project management need to pay attention to, including internal and external factors that affect projects, the use of appropriate methodologies and tools, and risk management. and effective communication. As we know, success in informatics project management is very important, considering the impact of project failure is very large and can have an impact on financial loss and organizational reputation.